Le marketing territorial participatif: approche synthétisée d’une participation citoyenne aux projets de développement local Etude de cas de dix (10) communes de la wilaya de Tizi Ouzou (Algérie) - Ghalem BENBRIKA; Faouzi GHIDOUCHE (المجلة الدولية للأداء الاقتصادي, 2021)
Through our present research, we will try to confirm if our municipalities use territorial governance that encourages participatory  democracy, the main goal is to understand the methods and strategies able to create a win-win relationship between administration and administered, a qualitative study of ten municipalities attached to the wilaya of Tizi Ouzou, was realized through a semi-structured interview guide, which allowed us to conclude that a citizen contribution is indeed achievable.